Experimental Evaluation of Various Chaos-based Image Encryption Schemes - Abubakar Abba; Nisar Ahmed; Hakeem Adewale Sulaimon (Journal of Computing Theories and Applications, 2025)
The widespread use of digital images, driven by low-cost, handheld acquisition devices, has increased the need for robust security measures to safeguard privacy. This demand is further underscored by rising identity theft and other image-related crimes. This study presents a chaos-based experimental evaluation of contemporary image encryption algorithms. Owing to intrinsic properties such as sensitivity to initial conditions and pseudo-randomness, chaos theory has become increasingly prominent in image encryption. Five chaos-based image encryption schemes were selected and applied to a dataset of 26 color images. The evaluation covers both encryption performance and cryptographic security. Decryption quality is measured using Mean Squared Error (MSE), Peak Signal-to-Noise Ratio (PSNR), Structural Similarity Index (SSIM), and DeepEns. Cryptographic security is assessed using entropy, correlation coefficient, Number of Pixel Change Rate (NPCR), Unified Average Changing Intensity (UACI), average and maximum deviation, and histogram analysis. Experimental results indicate that all evaluated schemes demonstrate strong cryptographic security and comparable encryption performance, with broadly similar effectiveness across methods.